Lithofacies And Depositional Analysis Environment Of West Section Kolok Nan Tuo Village, Sawahlunto City, West Of Sumatera - Cahyaningsih, Catur; Ritonga, Anjas Latif; Aldila, Shaury; Zulhikmah, Zulhikmah (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
Research areas were located in the west of Kolok Nan Tuo Village. Geographically this area is located at coordinates 00 ° 36'57,85 '' - 00 ° 37'56,89 '' latitude and 100 ° 42'10,08 '' 100 ° 43'47,28 " BT. The methods used in research is geological mapping. Based on the results of stratigraphic research area is divided into three units consist of: Crystalline Limestone Unit (SBGK) consisting Crystalline Limestone of and mudstone lithofacies, Conglomerate Units (SK) consists of polymic conglomerate and sandstones greywacke lithofacies while claystone Unit (SBL) lithofacies  consists of claystone with sedimentary structures is flake. Result of research can interpreted Depositional environment based on type of lithofacies include of grain size, sedimentary structures and content of fossils. SBGK interpretated  depositional environment is a basement of basin, SK depositional environment debris unit limestones can be seen from fragments of conglomerates that many there are crystalline limestones and mudstone that make up the alluvial fan (deposition surface) and lithologies clay from sedimentary structures where rock mudstone generally in doposition the current flow that quiet can form sedimentary structures flake and properties of claystone which carbonated an identifier depositional environments sea so can be determined that the environment in the form of neritic environment.